Use of gastroscopy in the management of pediatric toxic ingestions: insights from a decade of experience – a retrospective study - Marano, Marco; Di Meglio, Lavinia; Pisani, Mara; Goffredo, Bianca Maria; Olita, Carla; Faraci, Simona; Rea, Francesca; Perdichizzi, Salvatore; Zampini, Giorgio; David, Piero; Torroni, Filippo (Frontiers in Toxicology, 2026)
ObjectivePediatric poisonings account for a significant proportion of poison center consultations. Gastrointestinal decontamination (GD) is a crucial intervention in cases of acute poisoning, yet its effectiveness remains debated. This study aims to evaluate the role of esophagogastroduodenoscopy (EGD) in pediatric GD by retrospectively analyzing cases of suspected or confirmed toxic ingestions in which EGD was employed as a decontamination technique.MethodsA retrospective review was conducted on medical records from our hospital between 1 January 2015, and 31 March 2025. Pediatric patients (<18 years) who underwent EGD for GD following suspected or confirmed ingestion of toxic drugs were included.ResultsA total of 19 cases met the inclusion criteria. In all cases, a potentially toxic drug dose was ingested. EGD was primarily indicated in the presence of sustained-release (SR) formulations, delayed gastric emptying, or severe clinical presentation. In 15 cases, xenobiotic residues (pharmacobezoars, intact tablets, or gastric contents containing drug material) were successfully removed via EGD. No complications were reported, and all patients had favorable outcomes.ConclusionEGD appears to be an effective GD technique in selected pediatric poisoning cases, particularly those involving bezoar-forming drugs, SR formulations, and substances that impair gastrointestinal motility. It may also be useful in cases of massive ingestion of potentially harmful substances. Further research is needed to establish standardized guidelines for its use in pediatric toxicology.